2020
DOI: 10.1002/htj.21830
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer effect on an unsteady MHD radiative chemically reactive Casson fluid over a stretching sheet in porous medium

Abstract: The objective of the present study is to investigate the effects of the variable magnetic field, chemical reaction, thermal radiation, Soret effect, and variable heat absorption on the fluid flow and heat and mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The study's outcomes will be relevant to various warm frameworks such as microelectromechanical frameworks, warm exchangers, and cooling hardware, among others. 9,16,30,46 It will be interesting to note how important the use of electrical transducer processes, as well as bio-sensor devices, will be in the next generation.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study's outcomes will be relevant to various warm frameworks such as microelectromechanical frameworks, warm exchangers, and cooling hardware, among others. 9,16,30,46 It will be interesting to note how important the use of electrical transducer processes, as well as bio-sensor devices, will be in the next generation.…”
Section: Validationmentioning
confidence: 99%
“…Also, it is identified that human blood, jelly, honey, concentrated fruit juices, soup, and tomato sauce are illustrations of the Casson liquid model. [1][2][3][4][5][6][7][8][9] Heat and mass transfer with boundary layer stream across an accelerating surface/plate is a basic field of fluid dynamics with several application areas. Vertical plates/surfaces appear in wrapping dynamics, surface texture, spray coating, biological sterilization, electro-microfluidics, thermoplastic stretching, and other applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of heat and mass transmission past a parabolic starting infinite vertical plate was discussed by Agrawal et al 1 Das et al 2 studied unsteady MHD chemically reactive double‐diffusive Casson fluid past a flat plate in a porous medium with heat and mass transfer. Heat and mass transfer effect on an unsteady MHD radiative chemically reactive Casson fluid over a stretching sheet in porous medium explained by Das et al 3 Kataria and Patel 4 investigated the influence of thermodiffusion and parabolic motion on MHD second‐grade fluid flow with ramped wall temperature and ramped surface concentration. Mahanta et al 5 analyzed effects on MHD Casson stagnation point flow with stability analysis over the stretching surface in the presence of slip velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Alharbi et al 7 discussed the entropy generation of the MHD thermally radiative Eyring‐Powell fluid through an unstable oscillating porous stretchable surface. Das et al 8 examined the impact of Soret and variable heat absorption on unsteady chemically radiative MHD flows of the Casson fluid through a stretchable porous surface. Chamkha et al 9 investigated the entropy generation of the MHD mixed convective nanofluid flows in a gamma‐shaped porous cavity.…”
Section: Introductionmentioning
confidence: 99%